Variations in dynamic tumor-associated antigen-specific T cell responses correlate with HCC recurrence after thermal ablation - Zang, Chaoran; Zhao, Yan; Liu, Guihai; Li, Kang; Qin, Ling; Zhang, Yuewei; Sun, Jianping; Wang, Qi; Ma, Liang; Zhao, Peng; Sun, Yu; Guo, Dandan; et al. (Frontiers in Immunology, 2022)
Background Ablative therapy is a recommended treatment for hepatocellular carcinoma (HCC) not only for its effective eradication of tumors, but also for its induction of host immunity. However, the high 5-year recurrence rate after ablation underlines the poor understanding of the antitumor immunity response. Here, we investigated the effects of thermal ablation on antitumor immunity. Methods We analyzed the dynamics of tumor-associated antigen (TAA)-specific immune responses and changes in peripheral blood mononuclear cell phenotype in patients with HCC before and after tumor ablation. We used the IFN-γ ELISPOT assay and immunophenotyping by flow cytometry to evaluate the effects of ablation on host immunity. The correlation between the T cell response and disease outcome was explored to uncover the efficacy of the immune response in inhibiting HCC recurrence. Results Different TAA-specific T cell responses were identified among patients before and after ablation. One week after ablation, there was an improved immune state, with a switch from the dominance of an AFP-specific T cell response to that of a SMNMS-specific T cell response, which was correlated with better survival. Furthermore, an improvement in immune status was accompanied by a lower level of PD1+ and Tim3+ T cells in CD8+ T cells. Although this functional state was not durable, there was a higher degree of AFP-specific T cell responses at 4-weeks post-ablation. Furthermore, T cells presented a more exhausted phenotype at 4-weeks post-ablation than at the 1-week timepoint. Conclusions Ablation elicits a transient antitumor immune response in patients with HCC by changing the profile of the T cell response and the expression of immune checkpoint molecules, which correlated with longer recurrence-free survival of patients with HCC.